Modelo preditivo para o sucesso do desmame da ventilação mecânica invasiva - Carvalho, Camila Patrícia Galvão Patrício (2014)
Of critically ill patients in intensive care units (ICUs), about 40% develop acute respiratory failure (ARF) requiring invasive mechanical ventilation (IMV), which should be conducted as soon as possible for weaning, which may be defined as the process of transition from mechanical ventilation to spontaneous in patients who remain at MVI for more than 24 hours time. To consider that they had successfully weaned, the patient must maintain spontaneous ventilation for at least 48 hours after discontinuation of artificial ventilation. However, if the return to ventilatory support is needed in this period of 48 hours after extubation, called unsuccessful weaning. In clinical practice, patients are subjected to interruption of MVI, the passage through the spontaneous breathing trial (SBT) is recommended, achieving tolerate 30 minutes disconnected from ventilatory support without important clinical changes. The SBT is recommended as a diagnostic test to bring greater security to taking the patient off the machine decision. Although recommended, it is important to note that in studies, this test has not been shown to be accurate, not identified approximately 15% of weaning failure. The aim of this study is to propose a model to predict the success of weaning from mechanical ventilation to assist decision making for weaning in patients admitted to the Intensive Care Unit. This is an observational, longitudinal, prospective, quantitative and descriptive. 24 hours after the institution of MVI at the time prior to the SBT and the team after the withdrawal of MVI until the occurrence of the outcome of weaning success or failure: an instrument for data collection, divided into four periods was used. The statistical method of logistic regression was used to support decision making from clinical variables collected in the study. The clinical variables that were statistically significant (p-value <0.05) were: Tobin index between 51 and 105 (OR = 79.3); Sodium levels between 135 and 14 (OR = 20.3) and balances the Hydraulic balanced (OR = 9.6). The findings of this study present a valid logistic model, revealing the clinical variables that correlate with the success of weaning from invasive mechanical ventilation, thereby guiding decision making in this context.